The impact of patient-facing digital health interventions on patient safety outcomes: a meta-analysis of meta-analyses - Goran Erfani; Jemma McCready; Beckie Gibson; Alison Steven; John Unsworth; Heidi Siira; Erika Jarva; Kristina Mikkonen; Marco Tomietto (Oxford Open Digital Health, 2026)
Abstract Patient safety is a critical concern in healthcare, with preventable adverse events contributing significantly to morbidity and mortality. Digital health interventions (DHIs) are increasingly integrated into healthcare systems to improve patient safety outcomes. However, their effectiveness remains unclear. This study focuses on DHIs adopted by patients and, in detail, it aims to assess the effectiveness of patient-facing DHIs in improving patient safety outcomes, including medication adherence, healthcare utilisation, falls, mortality, adverse events, relapse rate, and readmissions. This meta-analysis of meta-analyses follows the PRISMA guidelines, and it is registered in PROSPERO. The eligible meta-analyses were identified across major databases (PubMed, Web of Science, Cochrane Reviews, EPISTEMONIKOS, CINAHL, ProQuest, Scopus, PsychARTICLES) from 2010 until 2024. The quantitative synthesis adopted a random-effects model. The corrected covered area method quantified the studies’ overlap and heterogeneity was assessed using the I2 statistic. Publication bias was examined using Egger's test. The JBI Critical Appraisal Checklist was adopted. In total 72 meta-analyses were included. Findings indicate that patient-facing DHIs improve medication adherence (SMD=0.33; 95%CI:0.22–0.44), reduce mortality risk (RR=0.84; 95%CI=0.78–0.90) and hospital readmissions (RR=0.90; 95%CI=0.81–0.98). Additionally, patient-facing DHIs reduce fall risk among older adults (SMD=0.30; 95%CI=0.13–0.46). However, the impact on healthcare utilisation reported increased patient visits, while relapse rate (RR=1.00; 95%CI=0.87–1.16) and adverse events (RR=0.94; 95%CI=0.66–1.34) showed no significant association with patient-facing DHIs. While these digital solutions demonstrate the potential to enhance medication adherence, reduce mortality, and prevent falls, their effectiveness varies. Challenges such as usability issues, digital literacy gaps, and infrastructure limitations should be addressed to optimise patient safety outcomes.